2016
DOI: 10.1161/hypertensionaha.116.07412
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Molecular Signatures in Hypertensive Patients With Renin–Angiotensin System Suppression

Abstract: A lbuminuria is a risk factor strongly associated with cardiovascular and renal complications particularly when diabetes mellitus and hypertension are present. However, in the absence of these 2 processes, albuminuria can be equally relevant as a predictor.1 These facts reflect the enormous relevance of albuminuria to monitor cardiovascular disease, the first cause of death in the general population.2 Different factors promote the development of albuminuria 3 and lead finally to an increased albumin leakage th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Urinary exosomes and their potential role in the physiopathological mechanisms responsible for albuminuria development in hypertensive patients under chronic RAS suppression were investigated. Quantitative iTRAQ-LC-MS/MS proteomic analysis was used to explore exosomal protein alterations, allowing deep coverage of the analyzed proteome as previously shown in plasma in this clinical setting [ 14 ]. The present work focused on proteins.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Urinary exosomes and their potential role in the physiopathological mechanisms responsible for albuminuria development in hypertensive patients under chronic RAS suppression were investigated. Quantitative iTRAQ-LC-MS/MS proteomic analysis was used to explore exosomal protein alterations, allowing deep coverage of the analyzed proteome as previously shown in plasma in this clinical setting [ 14 ]. The present work focused on proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Albuminuria is an indicator of cardiovascular risk and of end-stage renal disease. We recently reported significant alterations in proteins from urine and plasma in response to albuminuria and its de novo development in these hypertensive patients [ 14 , 16 , 17 ], demonstrating that subjacent biological mechanisms have a measurable molecular phenotype in biological fluids which, in some cases, may allow for anticipating the response of the traditional clinical marker (albuminuria). Exosomes have been shown to reflect molecular changes taking place in kidney tissue from patients with diabetic nephropathy [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is processed and presented by thymic antigen presenting cells and is likely to participate in shaping the T-cell repertoire [62], which is involved in the regulation of immune function [63,64]. SEMG-1 is upregulated in exosomes secreted by vascular endothelial cells under hypoxic stress conditions [65] and is considered as a new predictor of renal damage [66]. PIP also plays an important role in immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Plasma proteomic studies using LC-electrospray-trap MS have identified molecular signatures based on signaling molecules, growth factors, and angiogenesis factors that are predictive of renal disease in patients with hypertension and/or diabetes [76]. A comprehensive proteomic profiling study in 123 hypertensive patients with chronic RAAS suppression has found signatures that predict development of de novo development of albuminuria or indicate stable albuminuria [77]. The signatures were composed of proteins involved in inflammation, immune, and proteasome activation/endoplasmatic reticulum stress.…”
Section: Human Studiesmentioning
confidence: 99%